2016
DOI: 10.1186/s12879-016-2082-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance pattern: a report of microbiological cultures at a tertiary hospital in Tanzania

Abstract: BackgroundAntimicrobial resistance has been declared by the World Health Organization as a threat to the public health. The aim of this study was to analyze antimicrobial resistance patterns of the common pathogens occurring at the Bugando Medical Centre (BMC), Mwanza, Tanzania to provide data for antimicrobial stewardship programmes.MethodsA total of 3330 microbiological culture results scripts representing non-repetitive specimens reported between June 2013 and May 2015 were retrieved and analyzed for pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
55
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 28 publications
18
55
2
Order By: Relevance
“…As such the present study carried out an indebt study into the susceptibility patterns of the isolated pathogens and the outcome is quite worrying with the presence of multi-drug resistant pathogens in infected wounds of patients attending FMC, Yenagoa, as a result presenting a major risk. It is interesting though, that, despite the wide spread of resistance noticed amongst our isolates, they were all susceptible to amikacin and nitrofurantoin which is similar to the result documented previously [39][40][41][42], and in contrast to report by Pondei et al [12].…”
Section: Discussionsupporting
confidence: 90%
“…As such the present study carried out an indebt study into the susceptibility patterns of the isolated pathogens and the outcome is quite worrying with the presence of multi-drug resistant pathogens in infected wounds of patients attending FMC, Yenagoa, as a result presenting a major risk. It is interesting though, that, despite the wide spread of resistance noticed amongst our isolates, they were all susceptible to amikacin and nitrofurantoin which is similar to the result documented previously [39][40][41][42], and in contrast to report by Pondei et al [12].…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that about one third of S. aureus isolates were MRSA which is almost double to what was observed 10 years ago in the same setting among S. aureus isolates from wounds [24,25]. These findings cement the previous observations of increasing trend of MRSA in study settings made by Moremi et al in 2016 [26].…”
Section: Discussionsupporting
confidence: 85%
“…The study also found resistant pathogenic bacteria in the collected samples as previously reported by Nyambura et al, who did the study at BMC (20). Sadly, most of the blood samples collected in this study had resistant S. aureus which was suggestive of bloodstream infection as evidenced by more than 18% of patients who had fever.…”
Section: Discussionsupporting
confidence: 87%
“…The study found the overall resistance to clindamycin, cefipime and meropenem to be 70.1%, 72.4% and 8.5% respectively, which was higher than previous studies conducted in Tanzania (14,15,20).…”
Section: Discussioncontrasting
confidence: 70%